2020
DOI: 10.1101/2020.09.03.20187393
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Renin-Angiotensin-Aldosterone System inhibitors on outcomes of COVID-19 patients with hypertension: Systematic review and Meta-analysis

Abstract: Objective: This research aimed to systematically review and summarize the influence of Renin-Angiotensin-Aldosterone System (RAAS) inhibitors on the outcome of COVID_19 patients with hypertension. Methods: Electronic databases; PubMed/Medline, CINAHL, the Cochrane Central Register of Controlled Trials, clinical trial.gov, and Google Scholar were searched from 2019 to June 1, 2020. Additionally, the references of identified articles were also searched. Results: A total of 9 articles comprising 3,823 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Eight (66.7%) out of 12 systematic reviews found no association between the use of ACEI or ARBs and COVID-19 outcomes ( Table 6 and S6 Table) such as susceptibility to infection, hospitalization, severity and mortality, while some studies found no association even after adjusting for potential confounding factors [ 67 68 69 70 71 72 73 74 ]. However, in one study the use of RAASI was found to decrease the length of hospital stay [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eight (66.7%) out of 12 systematic reviews found no association between the use of ACEI or ARBs and COVID-19 outcomes ( Table 6 and S6 Table) such as susceptibility to infection, hospitalization, severity and mortality, while some studies found no association even after adjusting for potential confounding factors [ 67 68 69 70 71 72 73 74 ]. However, in one study the use of RAASI was found to decrease the length of hospital stay [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…In terms of number of COVID-19 related outcomes reported in each review, one outcome was reported by 13 reviews (27.7%) (18, 20, 21, 23, 24, 28, 29, 38, 39, 47, 52, 53, 61), two outcomes by 15 reviews (31.9%) (4, 17, 26, 31, 32, 34-37, 40, 42, 49, 54, 55, 58), three outcomes by 11 reviews (23.4%) (6, 22, 25, 27, 33, 44-46, 50, 56, 60) and 4-9 outcomes by eight reviews (17%) (19, 30, 41, 43, 48, 51, 57, 59). Overall, the 47 eligible reviews reported data on 18 unique pooled outcome estimates including death in 36 reviews, reviews (4, 6, 17-19, 22, 24, 25, 27, 30-39, 41-49, 54-56, 58-60), ICU admission in nine reviews (27, 28, 30, 41, 43, 48, 51, 56, 59), death/ICU admission as a composite outcome in 16 reviews (4, 20, 21, 23, 26, 29, 31, 32, 40, 41, 43, 45, 51, 55, 59), risk of acquiring COVID-19 infection in 15 reviews (19, 25, 27, 40<...>…”
Section: Resultsmentioning
confidence: 99%
“…Considering the critical domains, most reviews were considered to have had a satisfactory technique for the statistical combination of results (n=45, 95.7%) (4-6, 17-22, 24-57, 59, 60) and for assessing risk of bias (n=38, 80.1%) (4-6, 17, 19-23, 25-28, 30, 31, 34-38, 40-46, 48-53, 55-57, 59, 60). Less reviews were favourably considered in terms of accounting for risk of bias when interpreting and discussing the results (n=32, 68.1%), with appropriate conduct of publication bias (n=33) (4-6, 17, 19-21, 23-27, 30-33, 37, 38, 41-45, 47, 49-51, 53, 56, 57, 59, 60), and only 15 (31.9%) reviews referred to the review methods being established a priori (19, 22, 25, 26, 28, 30, 34, 37, 41-43, 52, 55, 56, 59).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations